Environmental Impacts of Agricultural Research: An Overview - CGIAR Standing Panel on Impact Assessment (CGIAR Standing Panel on Impact Assessment, 2012)
One of the four Impact Briefs summarizing final report and four case studies from the SPIA project on Assessing Environmental Impacts (2008-2011). More information on the project here (http://impact.cgiar.org/impacts/eia2008-2011).